Lego DC Comics super heroes. Aquaman : rage of Atlantis [videorecording (Blu-Ray + DVD)] - Kreig, Jim; Adams, Jeremy (Screenwriter) (Warner Bros. Home Entertainment, 2018)
After losing the throne of Atlantis, Aquaman must escape the threat of the Red Lanterns and learn what it means to be a hero, in order to save the Justice League and the entire planet!